“I Decided to Be a BRAVE English Speaker”: A Case Study of Learner Responses to a Global Englishes-informed Listening Curriculum Intervention - To, Calum; Rose, Heath (Journal of Studies in the English Language, 2026)
This multiple case study investigated learner responses to a Global Englishes-informed listening curriculum intervention targeting comprehension of varieties of English through explicit and implicit classroom exposure. Two adult learners engaged in the use of English as a Lingua Franca in their professional contexts took part in a four-week curriculum intervention introducing accents they had identified as important to their professional lives. A mixed-methods approach was employed, with data collected through participant logs and journals, interviews, and pre- and postclass activities eliciting numerical ratings of attitudes, comprehension, intelligibility, accentedness, and comprehensibility. Despite no improvement in numerical ratings, both learners developed new listening strategies, expressed increased confidence and evaluated the curriculum intervention positively, particularly explicit phonological instruction. The impact on attitudes was more mixed, with one participant expressing negative views about classroom exposure to varieties of English. Given positive affective outcomes, this study recommends teachers incorporate a wider range of English varieties into classroom activities. However, with the negative attitudinal impact potentially due to a lack of tasks encouraging engagement with global English use today, such exposure should be accompanied by critically reflective activities.